2013
DOI: 10.1248/bpb.b13-00509
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cytochrome P450 (CYP) <i>3A4*1G</i> Polymorphism on the Pharmacokinetics of Tacrolimus, Probability of Acute Cellular Rejection, and mRNA Expression Level of CYP3A5 Rather than CYP3A4 in Living-Donor Liver Transplant Patients

Abstract: Association between cytochrome P450 (CYP) 3A4*1G genotype of donors (n 412) and/or recipients (n 410), and the pharmacokinetics of tacrolimus and the risk of acute cellular rejection was examined in Japanese living-donor liver transplant patients between 2004 and 2011. The concentration/dose (C/D) ratio of tacrolimus in patients carrying graft liver with CYP3A4*1/*1 was significantly higher during 7 d after surgery than in that with CYP3A4*1/*1G (214 vs. 157 [ng/mL]/[mg/kg/day], p<0.01). After postoperative da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 21 publications
2
24
1
1
Order By: Relevance
“…Other genetic variants may explain additional variation in TAC dose requirement. As has been illustrated in adults, the drug transporter ABCB1, the CYP3A4, the human pregnane X receptor (NR1I2), interleukin 6 and COMT SNP may be associated with early TAC exposure [9] , [24] [26] . Although the association of ABCB1 , ACE with the C/D ratios of TAC was investigated, we didn’t observe any significant impact on TAC disposition in pediatric liver transplants ( Fig.…”
Section: Discussionmentioning
confidence: 93%
“…Other genetic variants may explain additional variation in TAC dose requirement. As has been illustrated in adults, the drug transporter ABCB1, the CYP3A4, the human pregnane X receptor (NR1I2), interleukin 6 and COMT SNP may be associated with early TAC exposure [9] , [24] [26] . Although the association of ABCB1 , ACE with the C/D ratios of TAC was investigated, we didn’t observe any significant impact on TAC disposition in pediatric liver transplants ( Fig.…”
Section: Discussionmentioning
confidence: 93%
“…It has been reported that CYP3A4*1G genotype in the graft liver contributes to the frequency of acute cellular rejection after transplantation 40 . Based on this evidence, we speculate that the expression profile of genes involved in drug metabolism in the graft liver, including CYP genes and genes studied in our work, may have impact on pharmacokinetics of drugs in liver transplant receipts.…”
Section: Discussionmentioning
confidence: 99%
“…LD was also observed in a clinical study investigating the influence of the CYP3A4*1G polymorphism on tacrolimus pharmacokinetics and CYP3A5 mRNA expression levels in 421 Japanese liver transplant patients. 35 The LD possibly explains some observations on the uncertain functional significance of this CYP3A4 variant. 9,34,35…”
Section: Additional Nonexonic Cyp3a4 Variantsmentioning
confidence: 99%
“…35 The LD possibly explains some observations on the uncertain functional significance of this CYP3A4 variant. 9,34,35…”
Section: Additional Nonexonic Cyp3a4 Variantsmentioning
confidence: 99%